1998
DOI: 10.1101/gad.12.18.2831
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage activates p53 through a phosphorylation–acetylation cascade

Abstract: Activation of p53-mediated transcription is a critical cellular response to DNA damage. p53 stability and site-specific DNA-binding activity and, therefore, transcriptional activity, are modulated by post-translational modifications including phosphorylation and acetylation. Here we show that p53 is acetylated in vitro at separate sites by two different histone acetyltransferases (HATs), the coactivators p300 and PCAF. p300 acetylates Lys-382 in the carboxy-terminal region of p53, whereas PCAF acetylates Lys-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
1,134
1
13

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,101 publications
(1,193 citation statements)
references
References 47 publications
40
1,134
1
13
Order By: Relevance
“…Several studies have shown the apoptotic role of p53 acetylation at the K320 residue (Sakaguchi et al ., 1998; Terui et al ., 2003; Roy et al ., 2005; Brandl et al ., 2012). In order to determine whether SIRT3 modulates p53 acetylation, we performed Western blot analysis after cotransfection of SIRT3 and p53 constructs in SH‐SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the apoptotic role of p53 acetylation at the K320 residue (Sakaguchi et al ., 1998; Terui et al ., 2003; Roy et al ., 2005; Brandl et al ., 2012). In order to determine whether SIRT3 modulates p53 acetylation, we performed Western blot analysis after cotransfection of SIRT3 and p53 constructs in SH‐SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, SIRT3 overexpression nullified the pathological changes induced by WT p53 and p53 K320Q, supporting our hypothesis that SIRT3 prevents p53‐induced mitochondrial dysfunction and neuronal cell death. Previous studies support our finding that p53 acetylation at the K320 residue is linked to cell damage (Sakaguchi et al ., 1998; Terui et al ., 2003; Roy et al ., 2005; Brandl et al ., 2012). Importantly, we found that Ac‐p53 K320 levels are significantly increased in the mitochondria of AD in conjunction with reduced SIRT3 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The parental HCT116 cells express a protein truncated downstream of the HAT domain (hence only detectable with the N-terminal antibody), which has been shown to be functionally normal (Sakaguchi et al, 1998;Sun et al, 2000;Iyer et al, 2004a). We have previously shown that the single HCT116 allele that is expressed was disrupted by homologous recombination, generating a p300 null cell line (p300 À ).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of human P53 at serine 392 and/or acetylation at lysine 382 occur after DNA damage (Hao et al, 1996;Lu et al, 1997;Sakaguchi et al, 1998). Silencing of BRG1 induced strong P53 activation, as observed in its phosphorylated and acetylated forms (Figure 7b).…”
Section: Genes Involved In Dna Repairmentioning
confidence: 89%